2014
DOI: 10.1177/1078155213514468
|View full text |Cite
|
Sign up to set email alerts
|

Multiple myeloma maintenance therapy: A review of the pharmacologic treatment

Abstract: Over the last decade, numerous drug therapies have emerged for the treatment of multiple myeloma including immunomodulating agents namely thalidomide, lenalidomide, and pomalidomide and proteasome inhibitors namely bortezomib and carfilzomib. These agents have transformed the treatment of multiple myeloma and the role of high-dose chemotherapy followed by stem cell transplantation in the treatment of the disease. There are now studies that evaluate the use of drug therapy as maintenance following autologous st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 68 publications
0
11
0
2
Order By: Relevance
“…The selection of maintenance therapy is a major decision for physicians. Currently, we do not have conclusive guidelines regarding the use of these agents [25]. Therapy with low-dose lenalidomide is the most widely used maintenance strategy for patients with MM after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…The selection of maintenance therapy is a major decision for physicians. Currently, we do not have conclusive guidelines regarding the use of these agents [25]. Therapy with low-dose lenalidomide is the most widely used maintenance strategy for patients with MM after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…In gegenwärtigen Metaanalysen und Reviewartikeln wurden neue und erfolgversprechende Therapiemöglichkeiten durch die Immunmodulatoren wie Thalidomid und Lenalidomid sowie die Proteasomeninhibitoren wie Bortezomib und Carfilzomib aufgezeigt, die ein breites Anwendungsspektrum durch die Kombinierbarkeit mit bisherigen klassischen Chemotherapeutika und Glukokortikoiden erlauben. Dies gilt nicht nur fĂĽr die Erstlinientherapie, sondern insbesondere fĂĽr die Rezidiv-und Konsolidierungstherapie [43].…”
Section: Diskussionunclassified
“…AuĂźerdem wird ausdrĂĽcklich auf das erhöhte Komplikationsrisiko fĂĽr Thromboembolien, PNP, Infektionen und Neutropenie hingewiesen [54]. Welches medikamentös basierte Behandlungsprotokoll fĂĽr die Erhaltungstherapie nach einer Stammzelltransplantation ausgewählt wird wie auch der geeignete Zeitpunkt und die Dauer hängen von vielen Variablen wie Applikationsform und -frequenz, Toxizitäten, Endorganfunktionen, Vorbehandlungen, Zytogenetik und Lebensqualität des Patienten ab [43,55,56].…”
Section: Erhaltungstherapie Und Konsolidierungstherapieunclassified
“…Tere have also been many advances in the use of maintenance therapy for MM patients. 21 Findings in earlier maintenance trials had shown an improvement in OS from continuing steroids such as single-agent oral prednisone at therapeutic doses for MM patients who had responded to initial therapy with steroids and chemotherapy. 22 Recent study fndings have suggested the beneft of other drugs as maintenance therapy for patients who completed their initial therapy.…”
Section: Maintenance Therapymentioning
confidence: 99%
“…22 Recent study fndings have suggested the beneft of other drugs as maintenance therapy for patients who completed their initial therapy. 21,[23][24][25] Specifcally, an improvement in OS with ongoing lenalidomide alone or with dexamethasone has been demonstrated in some but not all studies. [23][24][25] Unfortunately, studies with the PIs have not defned their role as maintenance drugs, 21 but the recent availability of the oral PI ixazomib will make the performance of these studies easier to undertake 7 .…”
Section: Maintenance Therapymentioning
confidence: 99%